Dalle politiche assistenziali alle social farms: note sul dare, ricevere e ricambiare nel sistema di welfare sulla disabilità - Stefano Onnis (EtnoAntropologia)
In this article I correlate the concept of gift ‒ referring to Marcel Mauss and his theory of giving-receiving-reciprocating ‒ with three specific areas in the field of intellectual disability: voluntary associations, cooperatives of social services and social cooperatives that promote employment opportunities for people with intellectual disability. My first analysis is that the social services are perceived by users with disability and their families as a donation that is afferent with the gift (and not in the sense of Marcel Mauss) rather than the law.